Emerging Trends and Future Directions for the Field of Motivation Psychology: A Special Issue in Honor of Prof. Dr. Willy Lens. Issue 3 (13th July 2016) - Vansteenkiste, Maarten; Mouratidis, Athanasios
This special issue is devoted to Prof. Dr. W. Lens, who passed away end of August 2014 while he was vacationing. The special issue is meant to honor Willy's intellectual contribution to the field of motivation psychology and his enthusiastic and devoted mentorship, which has spurred many of us to study motivation-related topics. In line with Willy's interest and extensive network, the special issue brings together scholars from diverse theoretical perspectives (i.e., Achievement Goal Theory, Future Time Perspective Theory, and Self-Determination Theory) and diverse cultural backgrounds (i.e., China, Peru, Greece, Portugal, Belgium, US, Australia, Canada). We introduce the special issue by highlighting four emerging trends that characterize contemporary motivation psychology and that were central to Willy's work: (a) multiperspectivism (i.e., a reliance on multiple motivational frameworks); (b) the diversity of motives and goals that underlie behavior (i.e., motivational heterogeneity); (c) interest in motives for non-participation; and (d) the issue of universalism versus relativism (i.e., the question whether there exist universal motivational processes or whether these processes are contingent upon sociodemographic, personality-based, and contextual factors). Each of the eight contributions in the special issue touch upon one or more of these emerging themes, which are critically discussed in conjunction with a number of directions for future research.